Effect of cylinder de-activation on the tribological performance of compression ring conjunction. (August 2017) - Bewsher, SR; Turnbull, R; Mohammadpour, M; Rahmani, R; Rahnejat, H; Offner, G; Knaus, O
The paper presents transient thermal-mixed-hydrodynamics of piston compression ring–cylinder liner conjunction for a 4-cylinder 4-stroke gasoline engine during a part of the New European Drive Cycle (NEDC). Analyses are carried out with and without cylinder de-activation technology in order to investigate its effect upon the generated tribological conditions. In particular, the effect of cylinder deactivation upon frictional power loss is studied. The predictions show that overall power losses in the piston–ring cylinder system worsen by as much as 10% because of the increased combustion pressures and liner temperatures in the active cylinders of an engine operating under cylinder deactivation. This finding shows the down-side of this progressively employed technology, which otherwise is effective in terms of combustion efficiency with additional benefits for operation of catalytic converters. The expounded approach has not hitherto been reported in literature.